Development of europium doped core-shell silica cobalt ferrite functionalized nanoparticles for magnetic resonance imaging. (February 2017) - Kevadiya, Bhavesh D.; Bade, Aditya N.; Woldstad, Christopher; Edagwa, Benson J.; McMillan, JoEllyn M.; Sajja, Balasrinivasa R.; Boska, Michael D.; Gendelman, Howard E.
Graphical abstract: Abstract: The size, shape and chemical composition of europium (Eu 3+ ) cobalt ferrite (CFEu) nanoparticles were optimized for use as a "multimodal imaging nanoprobe" for combined fluorescence and magnetic resonance bioimaging. Doping Eu 3+ ions into a CF structure imparts unique bioimaging and magnetic properties to the nanostructure that can be used for real-time screening of targeted nanoformulations for tissue biodistribution assessment. The CFEu nanoparticles (size ∼7.2 nm) were prepared by solvothermal techniques and encapsulated into poloxamer 407-coated mesoporous silica (Si-P407) to form superparamagnetic monodisperse Si-CFEu nanoparticles with a size of ∼140 nm. Folic acid (FA) nanoparticle decoration (FA-Si-CFEu, size ∼140 nm) facilitated monocyte-derived macrophage (MDM) targeting. FA-Si-CFEu MDM uptake and retention was higher than seen with Si-CFEu nanoparticles. The transverse relaxivity of both Si-CFEu and FA-Si-CFEu particles were r2  = 433.42 mM −1  s −1 and r2  = 419.52 mM −1  s −1 (in saline) and r2  = 736.57 mM −1  s −1 and r2  = 814.41 mM −1  s −1 (in MDM), respectively. The results were greater than a log order-of-magnitude than what was observed at replicate iron concentrations for ultrasmall superparamagnetic iron oxide (USPIO) particles (r2  = 31.15 mM −1  s −1 in saline) and paralleled data sets obtained for T2 magnetic resonance imaging. We now provide a developmental opportunity to employ these novel particles for theranostic drug distribution and efficacy evaluations. Statement of Significance: A novel europium (Eu 3+ ) doped cobalt ferrite (Si-CFEu) nanoparticle was produced for use as a bioimaging probe. Its notable multifunctional, fluorescence and imaging properties, allows rapid screening of future drug biodistribution. Decoration of the Si-CFEu particles with folic acid increased its sensitivity and specificity for magnetic resonance imaging over a more conventional ultrasmall superparamagnetic iron oxide particles. The future use of these particles in theranostic tests will serve as a platform for designing improved drug delivery strategies to combat inflammatory and infectious diseases.